1997
DOI: 10.1007/s002239900282
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Receptor Blockade Does Not Impair Bone Mineral Density in Adolescent Females

Abstract: The effect of peripheral androgen hypersensitivity on bone mineral density (BMD) was investigated in a group of adolescent women with idiopathic hirsutism (n = 17; mean age 17.0 +/- 1.7 years). The effect of long-term androgen-receptor blockade with flutamide (500 mg daily in two divided doses for 12 months) on BMD was assessed too. BMD was measured at lumbar spine (L2-L4) by a dual energy X-ray densitometer. Before flutamide treatment, patient BMD (1.14 +/- 0.07 g/cm2) was not significantly different from tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Animal studies revealed that female rats given flutamide displayed reductions in bone formation, whereas bone resorption remained unaffected (157,158). In addition, treatment of hyperandrogenic adolescent women with flutamide did not affect BMD, although biochemical markers were not determined in this study (159). Of interest, OHF which in vitro antagonized all effects of 5a-DHT on the hFOB/AR-6 cell line, including AR activation (43), proliferation (44) and differentiation (44), suppressed cytokine-induced IL-6 production to the same extent as 5a-DHT and, when co-administered with 5a-DHT, was not able to prevent 5a-DHT-induced IL-6 suppression (143).…”
Section: Effects Of the Anti-androgen Hydroxyflutamide (Ohf) On Bone mentioning
confidence: 53%
“…Animal studies revealed that female rats given flutamide displayed reductions in bone formation, whereas bone resorption remained unaffected (157,158). In addition, treatment of hyperandrogenic adolescent women with flutamide did not affect BMD, although biochemical markers were not determined in this study (159). Of interest, OHF which in vitro antagonized all effects of 5a-DHT on the hFOB/AR-6 cell line, including AR activation (43), proliferation (44) and differentiation (44), suppressed cytokine-induced IL-6 production to the same extent as 5a-DHT and, when co-administered with 5a-DHT, was not able to prevent 5a-DHT-induced IL-6 suppression (143).…”
Section: Effects Of the Anti-androgen Hydroxyflutamide (Ohf) On Bone mentioning
confidence: 53%
“…Testosterone administration improved BMD in such patients [2, 3, 24]. The bone effects of androgens may be due to a direct stimulation of androgen receptor at the bone level by testosterone itself or its 5α-reduced metabolite dihydrotestosterone or to stimulation of the estrogen receptor after local aromatization of testosterone to estradiol [10, 13, 20]. In fact, both androgen and estrogen receptors were present in human-derived osteoblasts [7, 25], and homogenized rat bone was able to aromatize testosterone into estrogens [26].…”
Section: Discussionmentioning
confidence: 99%
“…Each value represents the mean of two scans. In our laboratory, the in vivo coefficient of variation was <1.5% for healthy volunteer adolescents [20]. Apparent volumetric density (vBMD, g/cm 3 ) was calculated using the formula vBMD = aBMD × [4/(π × width)] [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flutamide has been used for long-term treatment continuing for months in adults with metastatic prostatic cancer. Experience with long-term use for 12 months in adolescents has demonstrated that the induced androgen blockade does not interfere with bone mineral density, 25 but the impact, if any, on sexual maturation of adolescent males has not been elucidated. Androgen blockade by flutamide in the doses as administered (10 mg/kg) is not complete, 26,27 and the experience with 6 weeks of treatment as noted in this study does indicate that clinically manifest derangements of sexual characteristics were occasional and minimal (transient breast tenderness), and reversible on cessation of treatment.…”
Section: Discussionmentioning
confidence: 99%